Augmented Reality in Solar System Learning at Primary School Level in Indonesia: A systematic literature review - Ariefka, Reza; Fauziah, Rosynanda Nur; Saputri, Agatha (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2023)
A systematic review of the use of AR in learning about the solar system in primary schools in Indonesia was conducted. This review identified 25 articles using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. We examined the tools used to develop AR, the type of AR used, the focus of the research, and the benefits of AR for solar system learning. Our findings show that the most commonly used tool for developing AR is Unity, and the most popular type of AR used is marker-based AR. Most of the research focuses on development and only a few on effectiveness and implementation. The use of AR is known to improve learning outcomes, critical thinking skills, scientific literacy, visual spatial skills and student curiosity. This systematic review provides researchers and educators with avenues for future research.